Relações entre autoritarismo e fracasso escolar: atitudes de agentes escolares profissionais e implicações na vida escolar de estudantes do ensino médio - Marcato, Célio Tiago (Universidade Federal de São Carlos, 2023)
This work was intended to establish a relationship between inappropriate professional school agents’ postures and negative implications in the students' school life, and also to set up guidelines for action in order to overcome these situations. For this, in light of the communicative methodology, conceptual investigations were carried out, through review and bibliographical survey, in national and international databases, in order to form a synthesized theoretical framework, aiming at definitions of concepts presented in the hypothesis of this research, precisely authoritarianism and school failure. Then, field research was carried out to identify inappropriate practices at school, focusing on authoritarian practices and actions, and their consequences in relation to attendance, performance, dropout and retention, the main evidence of school failure. As research subjects, we have established high school students from the Araraquara region, and as the main sample, we have defined students who graduated from regular high school between 2012 and 2017 and who are currently studying technical education. We have concluded that there are some opened and camouflaged practices of authoritarianism by professional school agents, such as disrespect, manifested by offenses to the student's cognitive capacity, class prejudice, unwillingness to dialogue and the chances of recovery. We have concluded, by extension, that these practices imply school failure, whether in attendance, performance, retention or, at the limit, dropout. Finally, in a propositional way, we have guided towards an action to overcome situations of authoritarianism from professional school agents in order to minimize the possibilities of school failure and, in effect, increase the possibilities of overcoming situations of social vulnerability.
Relationships between authoritarianism and school failure: attitudes of professional school agents and implications for the school life of high school students
Relaciones entre autoritarismo y fracaso escolar: actitudes de los agentes escolares profesionales e implicaciones para la vida escolar de los estudiantes de secundaria
Keywords: Autoritarismo; Autoritarismo na escola; Fracasso escolar; Sucesso escolar; Agentes escolares profissionais; Authoritarianism; Authoritarianism at school; School failure; School success; Professional school agents; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL